Third Generation Bioethanol Production from Chaetomorpha sp. isolated from Pulau Seribu Seawater using Acid Pretreatment - Sepwin Nosten Sitompul; Wafa Maftuhin (Fakultas Biologi | Universitas Jenderal Soedirman, 2020)
Currently, the primary source of energy based on fossil fuel, thus promoting both the excessive use of fossil fuel and global warming. Bioethanol provides sustainable energy and serves to reduce the dependence on using fossil fuel. Third-generation bioethanol production from macroalgae provides alternative green energy. To observe the potency of biofuel resources of Chaetomorpha sp. isolated from Pulau Seribu Seawater, the effect of the acid pretreatment was evaluated by using two different acids (H2SO4) concentrations. Powdered Chaetomorpha sp. was prepared, followed by acid pretreatment using H2SO4 1% and 2% (v/v). After 72 hours of fermentation, 1% H2SO4 pretreatment produced 0.026 % of the ethanol from 3 grams of Chaetomorpha sp., whereas pretreatment with H2SO4 2% did not produce bioethanol.